Devising Mixed-Ligand Based Robust Cd(II)-Framework From Bi-Functional Ligand for Fast Responsive Luminescent Detection of Fe3+ and Cr(VI) Oxo-Anions in Water With High Selectivity and Recyclability - Singh, Manpreet; Kumar, Gaurav; Neogi, Subhadip (Frontiers in Chemistry, 2021)
Environmental issue related applications have globally surfaced as hottest areas of research, wherein luminescent metal-organic frameworks (LMOFs) with functionalized pores put unique signature in real-time monitoring of multiple classes of toxic compounds, and overcome many of the challenges of conventional materials. We report a two-fold interpenetrated, mixed-ligand Cd(II)-organic framework (CSMCRI-11) [Cd1.5(L)2(bpy)(NO3)]·DMF·2H2O (CSMCRI = Central Salt and Marine Chemical Research Institute, HL = 4- (1H-imidazol-1-yl)benzoic acid, bpy = 4,4′-bipyridine) that exemplifies bipillar-layer structure with two different Cd(II) nodes, and displays notable robustness in diverse organic solvents and water. Intense luminescence signature of the activated MOF (11a) is harnessed in extremely selective and fast responsive sensing of Fe3+ ions in aqueous phase with notable quenching constant (1.91 × 104 M−1) and impressive 166 ppb limit of detection (LOD). The framework further serves as a highly discriminative and quick responsive scaffold for turn-off detection of two noxious oxo-anions (Cr2O72− and CrO42−) in water, where individual quenching constants (CrO42−: 1.46 × 104 M−1; Cr2O72−: 2.18 × 104 M−1) and LOD values (CrO42−: 179 ppb; Cr2O72−: 114 ppb) rank among best sensory MOFs for aqueous phase detection of Cr(VI) species. It is imperative to stress the outstanding reusability of the MOF towards detection of all these aqueous pollutants, besides their vivid monitoring by colorimetric changes under UV-light. Mechanism of selective quenching is comprehensively investigated in light of absorption of the excitation/emission energy of the host framework by individual studied analyte.